Training Techniques for Artisans to Improve Construction Project Performance in Edo State, Nigeria - Idowu, Ayobami Oluwaseun; Aigbavboa, Clinton; Oke, Ayodeji Emmanuel (International Journal of Sustainable Construction Engineering and Technology, 2024)
The emphasis placed on human resource development and utilization determines the development process of any nation. The poor quality of labour in Edo state compared to other cities has resulted in clients importing workers from other cities to carry out some trades and skills on their projects. This study aims to evaluate Artisan training techniques for improving construction project performance in Edo State, Nigeria. To accomplish this goal, the factors militating against artisans' training and techniques for artisans to improve their performance were also evaluated. A survey research design was used to collect data from professionals in the built environment in Edo state, using closed-ended questionnaires. A total of 162 questionnaires were distributed, with 108 being retrieved and deemed fit for analysis. The collected data were analyzed and presented as a percentile and mean score. The findings revealed that the major factors militating against the training of construction artisans are a lack of funds to organize training, the use of incorrect training techniques in the training, and a lack of motivation. The study also revealed that apprenticeship programs, trade testing courses, sponsored training systems, apprenticeship and coaching, conference training, on-the-job training techniques, and new technology trainings are required to improve the productivity of artisans. As a result, it was recommended that the government increase support for technical and vocational institutions, as well as training and retraining construction workers, in order to improve their performance.